Evaluating the effect of an Iranian traditional medicine-based herbal candy on body composition and appetite in overweight and obese adults: A preliminary study - Maryam Golzar; Effat Saghi; Hassan Rakhshandeh; Zahra Dehnavi; Ali Jafarzadeh Esfehani; Mohsen Nematy (Mashhad University of Medical Sciences, 2023)
Objective: Obesity is an important public health concern in the world. Considering the limited medications and their side effects and lack of a known effective way to reduce appetite, traditional herbs have been considered a complementary treatment for obesity. Therefore, this study was conducted to evaluate the effect of an Iranian Traditional Medicine (ITM)-based herbal candy on body composition and appetite in obese and overweight adults.Materials and Methods: In this preliminary study that conducted in nutrition clinic of Ghaem Hospital of Mashhad, participants were selected from overweight and obese people and randomly assigned to either groups. Participants in the intervention group received herbal candy which contained a combination of Portulaca oleracea, Plantago psyllium, and peanut oil, while participants in the control group received placebo candy for 8 weeks. The primary (appetite response, and weight changes) and secondary (body mass index (BMI), anthropometric parameters, blood pressure, and laboratory variables) outcomes were collected at baseline and during the intervention.Results: Fifty participants between the age of 18 and 65 years old were included in this study. Herbal candy resulted in a greater reduction in mean weight and BMI compared to placebo (p<0.001). Mean of hunger, satiety, and eating capacity indicators decreased more significantly at all three intervals (30 min after herbal candy, 1 hour after meal and 2 hours after meal) at lunch and dinner meal in the intervention group compared to the control group (p<0.05).Conclusion: A combination of produced herbal candy at a dose of 4 g (2 pcs), given half an hour before each meal for 8 weeks, can be effective in reducing weight and appetite in obese and overweight people.